The First International Conference on development finance & economic transformation Conference Proceedings [electronic resource] / editors : P Msweli ...[et.al.] - (:unkn) unknown (RSA : ICDFET, 2013., 2013)
Refer to document
Development ,Finance,Transformation & Economic Growth in Developing Countries for the 21st century.
Conference proceedings
Keywords: Economic transformation; Economic growth; Finance; 338.9091724; Conference proceedings -- South Africa -- Limpopo; Economic development; Economic policy